Pelatihan Internet Of Things dengan Database MySQL Bagi Siswa Kelas XII SMKS Bina Latih Karya - Selamet Samsugi; Styawati Styawati; M. Fitratullah; Feby Amanda; Dian Tri Saputra; Chafizd Chafizd; Fenty Ariany (Journal of Engineering and Information Technology for Community Service, 2023)
Based on the results of the situation analysis conducted at the Bina Latih Karya SMKS, problems can be solved through PKM. The problem is that the Internet of Things learning has not been implemented due to a lack of teachers who have the ability to teach the Internet of Things. The agency already has an IoT device but there is no implementation of learning yet. Based on the results of the Internet of Things training which has been attended by one class of SMKS Balai Latih Karya students, it can be concluded that this training can help the school in providing IoT material which has not been obtained in class so far. This training is also very interesting for students, marked by the enthusiasm of students in participating in this IoT training activity.